Cadena de valor en la pesca artesanal y su efecto en los beneficios económicos de los pescadores de la provincia de Pacasmayo, año 2018 - Sánchez Flores, Julia Isabel (2019)
The present research work was carried out with the purpose of studying the artisanal fishing sector in the province of Pacasmayo and to determine the way in which the Value Chain affects the economic benefits of the fishermen of said province in 2018.For its development the "descriptive" method was used, since the data collected was obtained from direct observation and from the application of surveys and interviews to those involved in the sector. In addition, the "nonexperimental" method was used because the activities related to the variables as they occur in their natural context are observed, and then analyzed. The population of the research is made up of the two existing associations in the province of Pacasmayo: the Mutual Association of Artisanal Fishermen of the Port of Pacasmayo and the San Pedro Pescador Association. The sample is made up of thirty-two fishermen from the first association and thirty-four fishermen from the second association respectively, finally having a sample made up of sixty-six fishermen. The conclusions that were obtained from the research are that artisanal fishing in Pacasmayo takes place informally and that its processes are not well defined; and that the Value Chain in artisanal fishing positively affects the economic benefits of fishermen in the region. province of Pacasmayo when its links are implemented properly.